Genetic Variability of Local Corn Cultivars from Kisar Island Southwest Maluku Regency using Microsatellite Molecular Marker - Hermalina Sinay; Ritha Lusian Karuwal (Biosaintifika: Journal of Biology & Biology Education, 2017)
This research aim was to reveal the genetic variability of local corn cultivars from Kisar Island using microsatellite molecular marker. The use of microsatellite markers is based on one reasons that the genetic information is polymorphic, and will be better to identify genetic diversity of plants including corn. Corn cultivars used were obtained from farmer in Kisar Island, and three reference varieties as outgroup were obtained from Institute of Cereals in Maros South Sulawesi. Polymerase chain reaction was conducted following the protocols from Fast Start kit (Qiagen-USA). The data obtained then analyzed with MVSP 3.1A Software for dendogram construction. The results showed that the appearance of DNA bands was vary (monomorphic and polymorphic) for local cultivars as well as reference varieties, with one or two bands on each primer. Based on the dendogram, there are three main clusters with similarity index ranged from 20% -100%. It can be concluded that there is very low similarity and distant kinship of local cultivars. The novelty of this research is knowing kinship relationship between local corn in Kisar Island which is not known yet. This results is expected to provide benefits regarding the breeding program, and for instance, it can be an important information regarding the development of local corn as a source in assembly the superior corn cultivars.